The Role of The School Committee on Infrastructure Management at Public Alementary School - Murni Yanto (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The school committee is a partner of the principal who has a role as a giver of consideration, as a supporter, as a supervisor, and as a mediator. All of these roles cannot stand alone but have a relationship between one role and another. In this study, the authors used a qualitative approach. The purpose of the article is to find out activities related to the objectives of the research. The subjects in this study were school committees, principals, teachers, and students' guardians. The results of the article are that the condition of facilities and infrastructure at the Karang Jaya 1 public elementary school is generally adequate, although there is still a shortage of supporting media such as projectors, the teaching and learning process is still not available.